2016
DOI: 10.2520/myco.66.1
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of ochratoxin A and ochratoxin B in commercial coffee in Vietnam and Thailand

Abstract: Occurrence of ochratoxin A (OTA) and ochratoxin B (OTB) in 32 Vietnamese roasted coffees, 30 Thai roasted coffees and 38 Thai instant coffees was performed using an immunoaffinity column-HPLC method. Twenty-six of Vietnamese roasted coffees were contaminated with overall average 0.75 μg/kg of OTA and 11 samples were contaminated with overall average 0.20 μg/kg of OTB. Four of Thai roasted coffees were contaminated with overall average 0.17 μg/kg of OTA and one sample was contaminated with 0.56 μg/ kg of OTB. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Since all 7 samples were supplied by the same manufacturer, it is possible that they were produced from a single batch of contaminated coffee. These results agree with those reported by majority of other authors: range 0.17–6.29 µg/kg, i.e., below the EC accepted limit [ 22 , 32 , 36 , 37 ]. However, Jonatova et al [ 25 ] reported somewhat wider range from 0.2 to 12.8 µg/kg (average 2.9 µg/kg), what means that the most contaminated samples exceeded the limit.…”
Section: Resultssupporting
confidence: 93%
“…Since all 7 samples were supplied by the same manufacturer, it is possible that they were produced from a single batch of contaminated coffee. These results agree with those reported by majority of other authors: range 0.17–6.29 µg/kg, i.e., below the EC accepted limit [ 22 , 32 , 36 , 37 ]. However, Jonatova et al [ 25 ] reported somewhat wider range from 0.2 to 12.8 µg/kg (average 2.9 µg/kg), what means that the most contaminated samples exceeded the limit.…”
Section: Resultssupporting
confidence: 93%
“…Under specific culture conditions, such as high sucrose (32%) in 2% yeast extract solution, levels of OTB and OTA production are comparable [ 24 ]. However, higher OTA than OTB concentrations have been detected in products such as cereals, cacao, and coffee [ 25 ]. In a few cases, such as in 11 of 20 samples of red wine from Spain, the OTB production level was found to be higher than that of OTA [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common method for the simultaneous determination of ochratoxin A and B is high performance liquid chromatography (HPLC) coupled with fluorescence detection (FD) [15][16][17][18][19][20][21] or mass spectrometry [22][23][24]. Besides common ELISA methods with spectrophotometric detection, immunosensors have recently become the subject of interest [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Besides common ELISA methods with spectrophotometric detection, immunosensors have recently become the subject of interest [25,26]. The largest extent of published works involves immunoaffinity columns [15,16,27] for sample preparation, often used in food control laboratories and routine practice. Immunoaffinity-based solid phase extraction (SPE) off-line coupled to HPLC-FD has been adopted as standard by authorities, particularly official method AOAC 2001.01 for wine and beer [28].…”
Section: Introductionmentioning
confidence: 99%